Chemical Composition and Biological Activities of Lagopsis supina Extract: Antioxidant, Adipogenic, and Ani-Inflammatory Effects - Juhyun Choi; Duc Dat Le; Nayoung Roh; Jiseok Lee; Deumaya Shrestha; Thientam Dinh; Vinhquang Truong; Badamtsetseg Bazarragchaa; Soo-Yong Kim; Sung-Suk Suh; Mina Lee; Jong Bae Seo (Pharmaceuticals)
Background/Objectives: Lagopsis supina, a traditional Chinese medicine valued for its diuretic properties, has limited research on its antioxidant, adipogenic, and anti-inflammatory effects. This study aimed to investigate the chemical composition and biological activities of Lagopsis supina extract (LSE). Methods: LSE was prepared and evaluated for antioxidant activity, effects on adipocyte differentiation in 3T3-L1 preadipocytes, and anti-inflammatory properties in RAW 264.7 macrophages. Ultra-high-performance liquid chromatography-electrospray ionization Orbitrap tandem mass spectrometry (UHPLC-ESI-Orbitrap-MS/MS)-based molecular networking was used to characterize its secondary metabolites. Results: LSE exhibited antioxidant activity in DPPH and ABTS assays. It significantly enhanced the differentiation of 3T3-L1 preadipocytes into mature adipocytes during early and intermediate stages by upregulating adipogenic transcription factors such as PPARγ, C/EBPα, and C/EBPβ, along with promoting cyclin E expression. LSE also increased PPARγ activity and the expression of its target genes, such as Glut 4, PEPCK, FABP4, and Plin2. Moreover, LSE inhibited lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophages by downregulating pro-inflammatory mediators (iNOS, COX-2, TNF-α, IL-6) and inhibiting extracellular signal-regulated kinase (ERK) phosphorylation. Chemical profiling revealed eight major compound groups: glycosides, organic acids, terpenoids, flavonoids, phenylglycosides, phenolics, fatty acids, and others characterized by their mass fragmentation patterns, precursors, and UV absorption spectra. In silico analysis confirmed these compounds’ bioactivities, demonstrating strong interactions and binding affinities with antioxidant, adipogenic, and anti-inflammatory protein targets. Conclusions: These findings highlight LSE’s triple therapeutic potential: antioxidant activity, adipogenesis promotion, and inflammation attenuation. LSE emerges as a promising therapeutic candidate for managing obesity and related inflammatory complications.